KARTY DYDAKTYCZNE - NOWE MEDIUM W NAUCZANIU MATEMATYKI - Dałek, Krystyna (Wydawnictwo Naukowe UAM w Poznaniu, 1997)
In the paper, the creation of new media for individualised learning of mathematics is presented. The actions research, during which these new materials, called didactic cards, arose are described. The experiments presented confirmed the assumption that individualised learning of mathematics in Polish schools is possible and feasible, if the appropriate media are adequately structured and prepared.
Keywords: Karty dydaktyczne; Nowe media; Multimedia; Indywidualizacja nauczania; Didactic charts; New media; Individualized education; Neodidagmata